Wittgenstein 's lectures (1983)
Desmod Lee (ed.). "Wittgenstein 's Lectures - Cambridge, 1930-1932." Chicago: The Chicago University Press, 1980.Wittgenstein's Lectures - Cambridge, 1932-1935. Ed. by AUce Ambrose, Chicago: The University of Chicago Press, 1979.